Marked attenuation of inflammatory mediator-induced C-fiber sensitization for mechanical and hypotonic stimuli in TRPV4-/- mice - Levine Jon D; Alessandri-Haber Nicole; Chen Xiaojie (SAGE Publishing, 2007)
Abstract Inflammatory mediators can directly sensitize primary afferent nociceptors to mechanical and osmotic stimuli. Sensitized nociceptors have a lowered threshold of activation and increased spontaneous activity, which result in symptoms of hyperalgesia and pain, respectively. The transient receptor potential vanilloid 4 (TRPV4) ligand-gated ion channel has been implicated in the hyperalgesia for mechanical and osmotic stimuli associated with inflammatory states. To investigate whether TRPV4 directly contributes to the mechanisms of inflammatory mediator sensitization of C-fiber nociceptors, we compared the effect of the injection of simplified inflammatory soup (prostaglandin E2 and serotonin) into the mechanical receptive fields of C-fibers in TRPV4+/+ and TRPV4-/- mice in vivo. Following the injection of the soup, the percentage of C-fibers responding to a hypotonic stimulus and the magnitude of the response was significantly greater in TRPV4+/+ mice compared to TRPV4-/- mice. Moreover, in response to simplified inflammatory soup only C-fibers from TRPV4+/+ mice exhibited increased spontaneous activity and decreased mechanical threshold. These marked impairments in the response of C-fibers in TRPV4-/- mice demonstrate the importance of TRPV4 in nociceptor sensitization; we suggest that TRPV4, as TRPV1, underlies the nociceptive effects of multiple inflammatory mediators on primary afferent.